THE IMPACTS OF THE OMISSION OF THE PUBLIC ADMINISTRATION IN THE FACE OF THE SALARY UPDATE OF PUBLIC SERVANTS (REMUNOM, 2024)
The remuneration of municipal public servants in Brazil often presents significant deficits in relation to the market and in view of the need, on the part of civil servants, to provide for their basic needs. Given this reality, the general objective of this work was to identify the main implications for public servants of the non-updating of salaries by the Public Administration. The methodology used was bibliographic research, carried out in books, scientific articles and legal texts. Aspects related to the correlation between the existential minimum and salary were discussed, understanding the indispensability of paying attention to the principle of human dignity. Conceptual aspects inherent to the budget and salaries in municipal public administration were also addressed, addressing legal aspects and the difficulties faced by municipal employees. Highlighting the scenario presented in Teófilo Otoni, it was possible to identify that the omission of the Public Power regarding the salary recovery of civil servants, which has lasted since 2016, means that they have harmed their purchasing power and, in general, access to basic rights , such as food, health, clothing, leisure, among others. The violation of the existential minimum by the public authorities, even if it can be suggested in view of the substantial loss of purchasing power of salaries that, at the time, were no longer adequate, proves to be insufficient for the Public Authorities to act to minimize such difficulties. Even though this does not constitute a violation of the constitutional requirement that the salary be not lower than the national minimum, there is an injury to a significant portion of employees, understanding that article 7, V, of the Federal Constitution, determines that it is worker's right to a minimum salary proportional to the extent and complexity of the work, among others that aim to improve their social condition. This improvement remains unfeasible given the omission presented here. Therefore, it appears that the impacts of the Public Administration's omission regarding the salary update of public servants concern the civil servants' access to the existential minimum and that this omission is unjustifiable, considering the substantial increase in revenues in the period analyzed.